A living cabinet of breath curiosities: somatics, bio-media, and the archive. Issue 3 (2nd September 2019) - Elswit, Kate
ABSTRACT: Breath builds intimate and physical connections beyond the individual, at the same time as it also poses challenges to sharing experience with others. However, performance has the capacity to archive multidimensional sensory experience and recompose it in a manner that is palpable to an audience. This essay addresses the problem of collecting, re-accessing, and sharing breath, from the indexing of breath as biodata to the use of 'breath media' in performance. The phenomenology of breath is interwoven with critical theorization of contemporary interactive biofeedback techniques, and grounded in reflexive analysis of creative practice, specifically the practice research project Breath Catalogue, in which experimental choreography and technology create a cabinet of breath curiosities in performance. This living catalogue – distributed between bio-media and somatic tasks of embodied memory – is contextualized within medical humanities, archive theory, choreographic practices, digital performance, and feminist technology studies.